A comparative diagnostic assessment of anterior tooth and bone status using panoramic and periapical radiography - Le Tina; Nassery Khash; Kahler Bill; Ao Geoffrey Heithersay (Sciendo, 2011)
Aims: The aim of the present study was to compare diagnostic assessments of anterior tooth and bone status in a randomised cohort of pre-orthodontic patients using panoramic and periapical radiographs.